A study on the microbial status of consumable fruit juices in Dhaka city and the comparative effects of preservatives on developing antibiotic resistance - Gomes, Rose Prema (Brac University, 2021)
This thesis is submitted in partial fulfilment of the requirements for the degree of Bachelor of Science in Biotechnology 2020.